Handbook of sustainable urban development strategies. - (:unkn) unknown (My University, 2020)
The Handbook of Sustainable Urban Development Strategies aims to develop methodological support to augment knowledge on how to implement integrated and place-based urban strategies under cohesion policy. In particular, it refers to Sustainable Urban Development (SUD) as supported by the European Regional Development Fund during the current programming period (2014-2020) and the upcoming one (2021-2027). In this context, the Handbook contains recommendations intended to complement official regulations, without being prescriptive. In fact, it is conceived as a policy learning tool, which should be flexible and adaptable to the needs arising from different territorial and administrative contexts. The Handbook addresses SUD strategies as bridges between cohesion policy on the one hand (with its rationale, rules and actors) and local territorial governance systems (with their rationale, rules and actors) on the other. The Handbook does not provide a ‘quick fix’, but rather provides suggestions - giving concrete examples and referring to existing tools and guidelines - on how to tackle key challenges during the process of strategy design, implementation and monitoring.. The Handbook targets local authorities (LA), managing authorities (MA) and all other relevant stakeholders involved in the process.
Keywords: Nachhaltige Stadtentwicklung; Implementierung; Integrierte Stadtentwicklung; Urban Governance; Finanzierung; Monitoring; Glossar